Evaluasi Penataan Parkir Pada Pasar Rakyat Di Kota Bengkulu - Edito Dwi Antoro (MAJALAH TEKNIK SIMES, 2021)
Abstract Along with the increasing population growth and the high level of the economy in an urban area or the increasing of an urban area towards a metropolitan city, it will result in an increasing need for facilities needed by urban communities such as business centers, education, offices and trade, so the need for parking lots increasingly widespread. The reason is because most people use vehicles a lot. This results in parking problems which are very important to be studied more deeply, because almost all activities in open spaces require parking facilities, including in the market area. Methods of data collection were carried out by main survey, Plate Matching Survey, Vehicle Number Survey, Vehicle Type Survey, Duration Survey Record entry / exit times of vehicles. A preliminary survey was conducted in order to find out the field conditions in the panoramic market area, kec. Singaranpati, Bengkulu city, Determining and dividing the research area into several points facilitates the survey of police number plates. After conducting a preliminary survey and piloting, it is followed by conducting a main survey. This main survey consists of the Parking Duration Survey (conducted at parking locations in the panoramic market, Singaranpati district, Bengkulu city) and the Atching Plate Survey carried out by recording the license plates of motorized vehicles (cars and motorbikes) that park at each observation point. , with time intervals every 1 (one) hour. At Pasar Panorama, the peak parking activity occurs on Sundays at Jalan Salak. The parking volume is 650 motorbikes, 65 cars, 2 trucks. The accumulated parking on Sundays is 30 motorbikes per hour, 22 cars per hour and 0 buses / trucks per hour. The parking duration for motorbikes is 88.3 hours, cars 1.48, buses / trucks, 2.3. Parking capacity with motorbikes is 0.72 per hour, cars 18.24 per hour, buses / trucks 13.85. Motorcycle parking index 2.17, car 0.81, nus / truck 0. Replacement time for motorbikes 2.17, cars 0.81 and buses / trucks 0. Parking space requirement for motorbikes 191, cars 0.32, buses / truck 0.01. Meanwhile, what happened on Jalan Kedondong on Sunday with parking volume was 698 motorbikes, 68 cars, 0 trucks. The accumulated parking on Sundays is 112 motorbikes per hour, 31 cars per hour and 0 buses / trucks per hour. Parking duration with motorbikes is 88.2 hours, cars 2.5, buses / trucks 0, parking capacity with motorbikes is 0.77 per hour, cars 10.8 hours, buses / trucks 0. Motorcycle parking index 1, 75%, cars 1.15%, buses / trucks 0. Replacement time for motorbikes 1.75, cars 1.15 and buses / trucks 0. Need for parking space on motorbikes 191, cars 0.32, buses / trucks 0 , 01.